2016
DOI: 10.5897/jdae2014-0627
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of integrated soil fertility management by groundnut farmers in Eastern Uganda

Abstract: Access to information and new technologies avails smallholder farmers an opportunity to improve their production decisions. However, access to information on technologies per se may not be relevant if the technologies are not adopted. This study was aimed at determining the factors that enable participants to access information on integrated soil fertility management (ISFM) technologies and to apply these technologies in groundnut production. It was conducted in the major groundnut producing districts of Toror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Farouque et al [44] identified farm size and media contact of farmers as significant predictors producing positive regression coefficients on the perception to use integrated soil fertility and nutrient management for crop production in Bangladesh. Besides, Jackline et al [45] provided supportive results that training and household size of farmers had been found to influence the decision to adopt improved technologies of soil fertility in Uganda.…”
Section: As Depicted In Tablementioning
confidence: 98%
“…Farouque et al [44] identified farm size and media contact of farmers as significant predictors producing positive regression coefficients on the perception to use integrated soil fertility and nutrient management for crop production in Bangladesh. Besides, Jackline et al [45] provided supportive results that training and household size of farmers had been found to influence the decision to adopt improved technologies of soil fertility in Uganda.…”
Section: As Depicted In Tablementioning
confidence: 98%
“…That is, a unit increase in farm size could result to a significant influence on the adoption of the improved rice varieties by .494 in the study area. Farm size was identified as an important socio-economic factor by (Jackline, 2002) in an adoption study of agricultural technologies.…”
Section: Factors Influencing the Adoption Of Strategies That Rice Far...mentioning
confidence: 99%
“…This means that the farmers who participate in more number of training, they are have more knowledge of catfish culture and feed management than those of farmers who didn't or participated less number of training. According to empirical data, training is a useful method for enhancing knowledge, especially when it comes to minimizing technology-related subjective uncertainty (Jackline et al, 2016;Nejadrezaei et al, 2018;Caffaro et al, 2020;Uddin et.al., 2022) [31,35,11,50] .…”
Section: Relationship Between the Selected Characteristics Of The Fis...mentioning
confidence: 99%